Factores de riesgo y su relación con infecciones respiratorias altas en niños menores de 5 años comunidad san Agustín cantón Babahoyo Los Ríos periodo septiembre 2017 a febrero 2018. - Erazo Ramos, Luis Manuel (2018)
The purpose of this research work is to determine the risk factors and their relationship with upper respiratory infections in children under 5 years of age; and create a program of free medical attention for treatments in respiratory therapy that manage to counteract the disease in time and reduce the risk of infant death. In the analysis of this research, an inductive-deductive method has been used to obtain information on the study variables; Therefore, a quantitative approach was carried out, by which the events presented in this study are detailed, this allowed to expose the problems caused by the risk factors in relation to ARI in children under 5 years of age and to look for possible solutions to improve the lifestyle of the inhabitants of the community. A field investigation was also carried out to obtain information through statistical data and perform the respective analysis of the acquired results to identify the validity of this research work. Through the research compiled, the risk factors and their relationship with the ARI were identified, taking into consideration that one of the problems they have is not having help from the government of free medical attention specialized in respiratory therapy, because they do not have economic income and a stable job to support the difficulties and treatments suggested by this disease, by which precautionary measures should be taken to control the disease in time and avoid life-threatening community.